Chitosan-Based Schiff Bases (CSBs) and Their Metal Complexes: Promising Antimicrobial Agents - Domenico Iacopetta; Alessia Catalano; Jessica Ceramella; Annaluisa Mariconda; Assunta D’Amato; Paola Checconi; Stefano Aquaro; Pasquale Longo; Maria Stefania Sinicropi (Molecules)
The scientific interest in the chemical modification of chitosan to increase its solubility and application has led to its conjugation with Schiff bases, which are interesting scaffolds endowed with diverse biological properties. The resultant chitosan-based Schiff bases (CSBs) are widely studied in scientific literature due to the myriad of activities exerted, both catalytic and biological, including anticancer, anti-inflammatory, antioxidant, and especially antimicrobial ones. Antimicrobial resistance (AMR) is one of the major public health challenges of the twenty-first century because it represents a threat to the prevention and treatment of a growing number of bacterial, parasitic, viral, and fungal infections that are no longer treatable with the available drugs. Thus, in this review, we present a brief outline of the biological activities of CSBs as well as their complexes with metals, with a particular focus on the recent literature regarding the antimicrobial effect of these captivating derivatives.